Antropometry Analysisi Of Stove Cooking Tofu Production On the Employee’s Safety And Convenience - Nita Ayu Ramdani; Budy Wiryono; Muanah Muanah (Universitas Muhammadiyah Mataram, 2021)
Ergonomics approach to vehicle design is emphasized on researching the limited capabilities of humans, both physically and mentally psychologically and their interactions in an integral human-machine system. Then systematically the ergonomics approach will then utilize this information for design purposes, so as to create a product system or work environment that is more suitable for humans. Objectives of the Research; Knowing the anthropometry of workers and the furnace knows the process of boiling tofu; determine the suitability of the anthropometry of workers with the tofu boiling process furnace; knowing the level of complaints felt by workers during the tofu boiling process. This study uses quantitative methods, with a descriptive analysis approach to the dimensions of the tofu boiling stove on the anthropometry of the workers' bodies. The instruments used in this research are literature study, observation and interviews. The variable used is the anthropometric data of workers in the manufacture of tofu. The dimensions measured include; hand width, the distance from the fingertips to the left to the right, the height of the hand grip from a vertical hand position up from standing upright, the distance from the hand grip to the back, the length of the hand, and the width of the palm. The body dimensions measured in the study are as follows: body height in standing position, shoulder height, elbow height, shoulder height in sitting position, elbow height in sitting position, shoulder width, hip width, body height in sitting position. The results of this study indicate that the measurement of the dimensions of the body of the community in the city of Mataram obtained varying results. The results of the measurement of body height when standing ranged from 131 to 153 cm and for the average body height of all people measured was 151 cm. Interviews on average workers complained of pain in the left elbow and right elbow and pain in the upper arm. left, right upper arm, right wrist and left wrist. By using the NBM questionnaire which is described in 27 points, the method of collecting data directly to workers by means of direct interviews on the spot is used